Criticism of The Fatherless Phenomenon From Rashid Rida’s Interpretive Perspective: A Thematic Study - Fatimah Azzahro; Agus Imam Kharomen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The phenomenon of fatherlessness has increasingly attracted scholarly attention as a complex social issue affecting family structures across different cultural contexts, including Muslim societies. Rather than assuming a uniform impact, contemporary research highlights that the absence or weakening of paternal roles whether physical or relational interacts with broader social and ethical dynamics in shaping children’s development. This study examines the concept of paternal leadership and responsibility in the Qur’an through a thematic (mawdū’ī) exegetical approach, with particular focus on Rashid Rida’s Tafsir al-Manār. Using qualitative library research, the study analyzes key Qur’anic passages related to fatherhood, including Q. 4:34, Q. 2:233, and Q. 31:13-19. The findings indicate that the Qur’an conceptualizes fatherhood as a multidimensional form of responsibility encompassing financial provision, moral guidance, and spiritual education. Rida’s interpretation frames paternal leadership not merely as authority, but as an ethical and socially embedded responsibility shaped by his reformist perspective. However, the study also shows that the application of this framework to contemporary contexts requires critical consideration, particularly in light of diverse modern era family structures. This research contributes to the development of socially engaged Qur’anic exegesis by offering a more integrative understanding of Islamic fatherhood that bridges textual interpretation and contemporary social analysis. It also provides a conceptual framework for re-evaluating paternal roles in Muslim families without reducing the issue of fatherlessness to a single causal explanation.